Perspectives of res development in Poland up to 2020 - Dolega, W. (Технічна електродинаміка, 2014)
This paper describes selected aspects of current development of renewable energy sources in Poland. Analysis and assessment of renewable energy sources in Poland is made. Perspectives of development of renewable energy sources up to 2020 in context of the implementation of the EU’s “3 x 20%” climate package by Poland and national quantitative target for RES development by year 2020 are described. Conclusions contain analysis of perspectives of development of renewable energy sources in Poland in the future. У роботі описуються окремі аспекти сучасного розвитку відновлюваних джерел енергії у Польщі, проведено аналіз та здійснена оцінка відновлюваних джерел енергії. Описані перспективи розвитку відновлюваних джерел енергії до 2020 року у контексті реалізації кліматичного пакету “3 x 20%” ЄС Польщею та національних кількісних цільових показників. Проаналізовано перспективи розвитку відновлюваних джерел енергії у Польщі в майбутньому. В работе описываются отдельные аспекты современного развития возобновляемых источников энергии в Польше, проведен анализ и дана их оценка. Описаны перспективы развития возобновляемых источников энергии до 2020 года в контексте реализации климатического пакета “3 x 20%” ЕС Польшей и национальных качественных целевых показателей. Проанализированы перспективы развития в будущем.